A A LITERATURE REVIEW OF HERBAL SUNSCREEN’S DOSAGE FORM AND SPF VALUE CLAIM - Rachmawati, Putriana; Sagala, Reynelda Juliani; Kambira, Pretty Falena Atmanda (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
The Indonesian government recommended sunbathing for 15 to 30 minutes in the morning to deal with the Covid-19 pandemic. Exposure to sunlight will activate the formation of vitamin D, which the body needs for defense against Covid-19 infection. However, excessive sun exposure will cause skin problems, including psoriasis, sarcoidosis, sunburn to skin cancer. One of the protections against sun exposure is the use of sunscreen. Sunscreen protects the skin from UV exposure by two mechanisms, namely, absorbing UV rays or reflecting UV rays. Currently, many sunscreens are developed with active substances derived from nature in various dosage forms. Sunscreen protection is stated using a photoprotector claim in the form of an SPF value or other supporting claims. This SPF value can be claimed using in vivo test, which previously could be predicted by on paper and in vitro approaches. Sunscreen safety is carried out by ensuring that the raw materials used comply with the requirements and penetration tests.